ANALISIS PENGARUH PARAMETER FISIK TERHADAP INDEKS KERENTANAN PANTAI (CVI) DI KAWASAN PANTAI BANDA ACEH DAN SEKITARNYA (STUDI KASUS PADA KAWASAN UJUNG PANCU SAMPAI UJUNG BATEE) - Veri Yanti; Ella Mailianda; Syamsidik Syamsidik (Prodi Magister Teknik Sipil Unsyiah, 2019)
A coastal area has important and vital influences on community’s lives due to the natural resource availability. The coastal area occurs any changes over time affecting the changes in the community and in the ecological perspectives. Banda Aceh is one of the coastal areas that has experienced several significant changes especially after earthquake and tsunami on December, 26th 2004. Due to the condition, it is required to analyze coastal vulnerability in Banda Aceh and neighbor. This research was aimed to investigate the influences of physic parameters consisting of hydrodynamic and morphology parameters on determining Coastal Vulnerability Index (CVI). The analysis will determine the coastal vulnerability index in one year period. The analysis was carried out in the northern coast of Aceh Province, between Ujong Pancu and Ujung Batee by dividing the areas into 5 (five) cells bordered by natural morphology feature such as inlet, headland, river estuary, and lagoon. Based on 6 (six) physical parameters used on coastal vulnerability index (CVI) determination, it is obtained that 2 cells have low risk potential (green), which are Cell 1 and Cell 3 with the CVI values are 2.45 and 3.0, respectively. Cell 2 has moderate risk potential (yellow) with CVI value is 4.24. Meanwhile, Cell 4 and Cell 5 have high risk potential (red) with CVI values are 5.20